Les plages de la côte d'Ejjehmi-Soliman (golfe de Tunis, Tunisie) : exemple d'accélération de l'érosion marine dans une cellule sédimentaire artificiellement tronçonnée - Wissem Marzougui; Ameur Oueslati (Physio-Géo)
The issue of beach erosion in the coast of Ejjehmi-Soliman, located in the bottom of the Bay of Tunis between the Seltene wadi and the channel that connects the sebkha Soliman to the sea, has been the subject of some studies. They indicated that the general trend is giving advantage to the sea. But the period considered, particularly in studies that have focused on the quantification of the mobility of the shore, was relatively short (between 1962 and 1996) and doesn't took into account neither the most recent evolution nor the situation before the extension of coastal managements.This work, by considering a longer period (1948-2016), concluded to the existence of situations significantly different through time. The erosive trend has begun to emerge by the 1970s. But the most rapid rhythms of the shore retreat are in relation with the creation of breakwaters, in 1989-90, to protect the managements established on the seafront. The implementation of these protection structures led to a segmentation of the coast which passed from a united sediment cell to a juxtaposition of small cells delimited by protected areas. In each of them, the erosion is not uniform and the zone of maximum erosion moves according to the shore evolution. Finally, the shore adaptation to the sea advance highlights the role of coastal dunes in maintaining a beach. Dunes that have not yet been colonized must be preserved from building extension.